Solid lipid nanoparticles loaded with iron to overcome barriers for treatment of iron deficiency anemia - Hosny, Khaled Mohamed (Drug Des Devel Ther, 2015)
According to the World Health Organization, 46% of the world’s children suffer from anemia, which is usually treated with iron supplements such as ferrous sulfate. The aim of this study was to prepare iron as solid lipid nanoparticles, in order to find an innovative way for alleviating the disadvantages associated with commercially available tablets. These limitations include adverse effects on the digestive system resulting in constipation and blood in the stool. The second drawback is the high variability in the absorption of iron and thus in its bioavailability. Iron solid lipid nanoparticles (Fe-SLNs) were prepared by hot homogenization/ultrasonication. Solubility of ferrous sulfate in different solid lipids was measured, and effects of process variables such as the surfactant type and concentration, homogenization and ultrasonication times, and charge-inducing agent on the particle size, zeta potential, and encapsulation efficiency were determined. Furthermore, in vitro drug release and in vivo pharmacokinetics were studied in rabbits. Results indicated that Fe-SLNs consisted of 3% Compritol 888 ATO, 1% Lecithin, 3% Poloxamer 188, and 0.2% dicetylphosphate, with an average particle size of 25 nm with 92.3% entrapment efficiency. In vivo pharmacokinetic study revealed more than fourfold enhanced bioavailability. In conclusion, Fe-SLNs could be a promising carrier for iron with enhanced oral bioavailability.